1987
DOI: 10.1897/1552-8618(1987)6[857:aocofb]2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Contamination of Fish by Water-Soluble Fractions of Petroleum: A Role for Bile Metabolites

Abstract: Several conjugated metabolites were found to accumulate in the gall bladder bile of trout (Salmo gairdneri) exposed to No. 2 fuel oil, but no free metabolites could be detected. GC-MS analysis of the major resolved components resulted in the identification of at least eight metabolites, present as alcohols. Single-ion monitoring MS indicated the predominance of a fragment at m/e 152, and 'H-NMR spectroscopy provided information on the average structure of the mixture of hydrolyzed metabolites. The study demons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

1989
1989
2001
2001

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 5 publications
(5 reference statements)
0
9
0
Order By: Relevance
“…Oxidation products are formed in the first stage, and these compounds further react to form various conjugates such as glu-coronides, sulphates, or amino acid or glutathione derivatives (Hellou et al, 1989;Hellou and Upshall, 1995). These more polar derivatives can then be eliminated from the organisms through the gall bladder bile (Hellou and Payne, 1987). In vertebrates, these reactive first phase oxidation products also can react with macromolecules (such as DNA) to form adducts that interfere with biochemical processes and can ultimately cause cancer.…”
Section: Metabolismmentioning
confidence: 99%
“…Oxidation products are formed in the first stage, and these compounds further react to form various conjugates such as glu-coronides, sulphates, or amino acid or glutathione derivatives (Hellou et al, 1989;Hellou and Upshall, 1995). These more polar derivatives can then be eliminated from the organisms through the gall bladder bile (Hellou and Payne, 1987). In vertebrates, these reactive first phase oxidation products also can react with macromolecules (such as DNA) to form adducts that interfere with biochemical processes and can ultimately cause cancer.…”
Section: Metabolismmentioning
confidence: 99%
“…The quantities of metabolites reported above represent the material detected in the bile 7 d after a single exposure and depend on the level of initial exposure as well as on the rate of production and release of the metabolites. It has been previously shown that these rates vary from compound to compound [15]. The level of exposure was 4 mg/fish for six of the PACs, 2 mg/fish for carbazole, and 1 mg/fish for chrysene.…”
Section: Resultsmentioning
confidence: 94%
“…This could be due either to low PAH content in the diluted effluent or to an insufficient exposure period for PAHs to achieve steady-state concentration in the fish. Bile fluorescence has been previously shown to be a very sensitive indicator of PAH exposure in fish, and has been correlated with specific toxic PAHs such as benzo(a)pyrene (Hellou and Payne, 1987;Britvic et al, 1993;Krahn et al, 1993;Upshall et al, 1993). However, most of these studies were carried out using fish that had experienced long-term exposure to polluted water or sediment.…”
Section: Resultsmentioning
confidence: 99%
“…A 25 p L aliquot was removed and diluted to 1 mL prior to measuring fluorescence on a Hitachi F-4500 fluorescence spectrophotometer. The excitation/emission wavelength pairs 290/335, 280/385, 256/380, and 380/430 nm were selected (Hellou and Payne, 1987;Krahn et al, 1993;Upshall et al, 1993), and correspond to the analysis of naphthyl glucuronides, conjugate cleaved naphthyls, phenanthrenes and their metabolites, and benzo(a) pyrene and its metabolites, respectively.…”
Section: Bile Fluorescencementioning
confidence: 99%